Hypoxia induces robust ATP release from erythrocytes in ApoE-LDLR double-deficient mice - Alcicek, Fatih Celal; Dybas, Jakub; Bulat, Katarzyna; Mohaissen, Tasnim; Szczesny-Malysiak, Ewa; Franczyk-Zarow, Magdalena; Marzec, Katarzyna M. (Frontiers in Physiology, 2024)
Red blood cells (RBCs) play a role in the regulation of vascular tone via release of adenosine triphosphate (ATP) into the vasculature in response to various stimuli. Interestingly, ApoE/LDLR double-deficient (ApoE/LDLR−/−) mice, a murine model of atherosclerosis, display a higher exercise capacity compared to the age-matched controls. However, it is not known whether increased exercise capacity in ApoE/LDLR−/− mice is linked to the altered ATP release from RBCs. In this work, we characterized the ATP release feature of RBCs from ApoE/LDLR−/− mice by exposing them to various stimuli in vitro. The results are linked to the previously reported mechanical and biochemical alterations in RBCs. 3V-induced ATP release from RBCs was at comparable levels for all groups, which indicated that the activity of adenylyl cyclase and the components of upstream signal-transduction pathway were intact. Moreover, hypoxia- and low pH-induced ATP release from RBCs was higher in ApoE/LDLR−/− mice compared to their age-matched controls, a potential contributing factor and a finding in line with the higher exercise capacity. Taken together, augmented hypoxia-induced ATP release from RBCs in ApoE/LDLR−/− mice indicates a possible deterioration in the ATP release pathway. This supports our previous reports on the role of the protein structure alterations of RBC cytosol in hypoxia-induced ATP release from RBCs in ApoE/LDLR−/− mice. Thus, we emphasize that the presented herein results are the first step to future pharmacological modification of pathologically impaired microcirculation.